2013
DOI: 10.1177/2049463713507910
|View full text |Cite
|
Sign up to set email alerts
|

A community pain service solution-focused pain management programme: delivery and preliminary outcome data

Abstract: Summary points:1. This article introduces a rationale for a solution-focused approach to a community-based pain management programme (PMP), describing delivery and preliminary outcome data. 2. It suggests PMPs can be feasibly run in the community without necessity for hospital care setting. 3. A community setting is also advantageous in that it allows maintenance of social networks and close third-sector links to support long-term, sustained mental well-being. 4. Solution-focused psychological approaches help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…Significant increases in participants' levels of meaning (i.e., purpose in life) were also noted in the second of the studies reported in the paper (Study B;Howell et al 2015), though no such increases were found in the first (Study A; Howell et al 2015). Of these studies which measured well-being as an outcome variable, only Simm et al (2014) investigated the longer-term effects of the PPI employed, with significant improvements maintained at ten-week, six-month and 12-month follow-ups.…”
Section: Well-beingmentioning
confidence: 78%
See 1 more Smart Citation
“…Significant increases in participants' levels of meaning (i.e., purpose in life) were also noted in the second of the studies reported in the paper (Study B;Howell et al 2015), though no such increases were found in the first (Study A; Howell et al 2015). Of these studies which measured well-being as an outcome variable, only Simm et al (2014) investigated the longer-term effects of the PPI employed, with significant improvements maintained at ten-week, six-month and 12-month follow-ups.…”
Section: Well-beingmentioning
confidence: 78%
“…Three studies, described in two publications (Howell et al 2015;Simm et al 2014), evaluated the impact of PPIs upon psychological well-being, with all reporting significant increases immediately following intervention. It is noteworthy that the articles by Simm et al (2014) and Howell et al (2015) comprised the lowest and highest scoring papers on the QATSSD respectively. When the three individual subscales of the well-being measure reported in Howell et al's (2015) two studies were investigated, significant increases in relation to the pleasure experienced by the participants, and sense of engagement in life were observed.…”
Section: Well-beingmentioning
confidence: 99%
“…However, quantitative analysis of the PMP involved in the present research suggests positive change can be maintained for up to 12 months upon both measures of statistical and clinical significance. 9 …”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…22,23 Given the paucity of research examining SF approaches in physical health settings, this study aimed to broadly explore the experiences of patients who had attended an 8-week SF PMP in a community setting. It was hoped that qualitative practice-based evidence could aid the interpretation of outcome data 9 and reveal elements of the programme participants experienced as significant.…”
Section: Introductionmentioning
confidence: 99%
“…Las intervenciones psicológicas utilizadas así como los tamaños de efecto encontrados varían de acuerdo a los estudios, aunque suelen ser tamaños de efecto moderados. En cuanto al mantenimiento de los cambios a largo plazo, los resultados son mixtos (Simm, Iddon y Barker, 2014;Flink, Smeets, Bergbom y Peters, 2015;Muller y cols., 2016). Es importante tener en cuenta también que la mayoría de estos estudios no incluyeron un grupo control, y por lo tanto sus resultados deben analizarse con precaución.…”
Section: Nuevos Abordajes Terapéuticos Para El Tratamiento De La Fibrunclassified